Removal of Arsenic (V) from Water Using Hierarchical Flower-Shaped AlOOH/Fe Micro/Nanostructures - Bakina O. V. Olga Vladimirovna; Glazkova E. A. Elena Alekseevna; Svarovskaya N. V. Natalia Valentinovna; Berenda A. V.; Lozhkomoev A. S. Aleksandr Sergeevich; Lerner M. I. Marat Izrailyevich (2015, 2015)
Title screen